Strategi Komunikasi Visual dalam User Interface (UI) dan User Experience (UX) Untuk Membangun Kepuasan Pengguna - Abdul Kholik; Asep Soegiarto; Wina Puspita Sari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
In the current digital era, visual communication is crucial as users rely on interfaces to interact with various platforms. User Interface (UI) and User Experience (UX) design are key components in creating effective visual communication. UI focuses on appearance and aesthetics, while UX pertains to the overall user experience. This study employs a qualitative method through literature review, analyzing relevant written sources such as books and journals to identify findings and principles related to UI and UX. The process involves selecting credible sources and conducting critical analysis of the obtained information. The conclusion of this research indicates that the integration between UI and UX is essential for enhancing effectiveness and user satisfaction in visual communication. By applying user-centered design principles, designers can create digital experiences that are both appealing and functional, thereby increasing user engagement and loyalty.